Every man for himself = Sauve qui peut (la vie) - Yared, Gabriel 1949- (<<The>> Criterion Collection, 2015)
"After a decade in the wilds of avant-garde and early video experimentation, Jean-Luc Godard returned to commercial cinema with this star-driven work of social commentary, while remaining defiantly intellectual and formally cutting-edge. "Every man for himself", featuring a script by Jean-Claude Carrière and Anne-Marie Miéville, looks at the sexual and professional lives of three people-a television director (Jacques Dutronc), his ex-girlfriend (Nathalie Baye), and a prostitute (Isabelle Huppert)-to create a meditative story about work, relationships, and the notion of freedom. Made twenty years into his career, it was, Godard said, his "second first film". [criterion.com]
Aspect ratio 1.66:1. - New high-definition digital restoration
Orig.: Frankreich, Österreich, Deutschland, Schweiz 1980
Enth. scénario de "Sauve qui peut (la vie)" (1979), a short video created by director Jean-Luc Godard to secure financing for "Every man for himself" ; new video essay by critic Colin MacCabe ; new interviews with actor Isabelle Huppert and producer Marin Karmitz ; archival interviews with actor Nathalie Baye, cinematographers Renato Berta and William Lubtchansky, and composer Gabriel Yared ; two back-to-back 1980 appearances by Godard on "The Dick Cavett Show" ; "Godard 1980", a short film by Jon Jost, Donald Ranvaud, and Peter Wollen, featuring Godard ; trailer ; new english subtitle translation ; an essay by critic Amy Taubin